Inhibited Production of iNOS by Murine J774 Macrophages Occurs via a phoP-Regulated Differential Expression of NFκB and AP-1 - Scott D. Hulme; Paul A. Barrow; Neil Foster (Interdisciplinary Perspectives on Infectious Diseases)
Background. There are no reported data to explain how Salmonella suppress nitrite ion production in macrophages or whether this phenomenon is unique to typhoidal or non-typhoidal serovars. The aims of this study were, therefore, to investigate these phenomena. Methods. We measured survival of S. typhimurium 14028 and its phoP mutant in murine J774 macrophages, cultured with or without interferon gamma. We compared expression of inducible nitric oxide synthase (iNOS) mRNA and protein, and nitrite ion production and also examined binding of nuclear factor 𝜅B (NF𝜅B) and activator protein 1 (AP-1) to macrophage DNA. Results. S. typhimurium 14028 inhibited binding of NF𝜅B and AP-1 to DNA in murine J774. A macrophages via an intact phoP regulon. This correlated with increased survival and reduced iNOS expression. Suppression of NF𝜅B activity was ameliorated in macrophages cultured with IFN-γ and this correlated with increased expression of iNOS mRNA and nitrite ion production, although IFN-γ had no effect on AP-1/DNA interaction. We show, that with one exception, suppression of iNOS is unique to typhoidal serovars. Conclusion. S. typhimurium inhibit NF𝜅B and AP-1 interaction with macrophage DNA via the PhoP regulon, this reduces nitrite ion production and is principally associated with typhoidal serovars.